Dilemmas about Colombian participation in the international Cannabis trade - Bejarano Daza, José Ignacio; Correa Martínez, César Alberto (Scientific journal of social studies, 2022)
This research seeks to ref lect on the current state of Colombia’s participation in the international cannabis market. This in light of the most recent norm issued by the Colombian government in this matter. To this end, I plan to take a historical look at several of the legal orders issued in Colombia in relation to cannabis and to make a comparative exercise with the legal systems developed in Canada and Uruguay. The research will allow us to analyze the issue beyond the legal text embodied in the law, including the public position and organs of power and, in this way, approaching the processes that preceded the issuance of these norms and the connotation that these legal transformations have had in the participation of these countries in the international cannabis market.